Formation and development of the educational system of the Оrenburg region in the XVIII–XIX centuries - S. V. Lyubichankovskiy (Вестник Самарского университета: История, педагогика, филология, 2020)
In the article, the author presents an analysis of the formation and development of the educational system of the Orenburg region during the period from the establishment of the Orenburg province and up to the entry of the Russian Empire during the revolutionary upheavals of the early XX century. The main stages of this process are highlighted: the appearance of the first educational institutions in the conditions of the formation of the Orenburg region as a new administrative space of the Russian Empire (1730s 1770s); the development of the educational system of the Orenburg region in the conditions of stabilization of the frontier zone and systematization of the state educational policy (late XVIII mid XIX century); the development of the educational system under the conditions of post-reform modernization (second half of the XIX early XX century). He revealed the key reasons for the change in the educational system related to the specific needs of the region and changes in state policy in the field of education. He concluded that during the period under study, the educational system of the Orenburg region simultaneously solved two key tasks providing the region with educated personnel and the formation of a loyal stratum of foreign (national) intelligentsia. The research is based on both archival (from the funds of the State Archives of the Orenburg region) and published historical sources.